Infográfico : a dimensão dissertativa da imagem na cultura contemporânea - Carmo, João Paulo de Oliveira (2023)
The contemporary concept of infographic refers to structures that combine elements of visual language and verbal language to inform about the most varied subjects and themes. Infographics gained notable popularity at the end of the 20th century, especially in the field of journalism, when the public intensified the demand for new communication approaches capable of offering a more immersive and complete experience regarding information. Starting from the theoretical axis that understands communication as culture, an investigation is made into the dissertation capacity of the visual language of infographics, that is, the property of establishing concepts and formulations through the images that constitute these productions. Based on an interdisciplinary dialogue between theorists, researchers and professionals working in the most diverse areas, this work investigates the factors that allow dissemination through images, analyzing the recent history of infographics, the knowledge associated with the formation of this field, planning techniques and creating graphic pieces and concepts and reflections relating to studies on language, message and image within the scope of contemporary culture. This work also includes a laboratory practice of producing infographics, as a way of materializing the results obtained through the questions raised throughout the research.